The Effect Of PER and Dividend Yield On Banking Share Prices The Idx In 2020 - Syarif Hidayah Lubis; Agus Defri Yando (JURNAL AKUNTANSI BARELANG, 2021)
The purpose of this study is to see the effect of PER and Dividend Yield on banking stock prices in 2020. The method used in this study is a quantitative type using secondary data using a target population of 44, while for the determination of the population of the Non-Sampling type. The probability is 16 and the analysis used is SPSS version 22. The results in this study found that PER partially has no effect on share prices, dividend yield partially has no effect on price Shares, PER and Dividend Yield simultaneously have no effect on Stock Prices.